Mengembangkan Kemampuan Sosial Anak Usia 4-5 Tahun Melalui Permainan Kartu Bergambar di TK Al Hamidy Mataram - Wahyuni, Laela (Jurnal Paedagogy, 2020)
The purpose of this study was to develop the social abilities of children aged 4-5 years through pictorial card games at TK Al Hamidy Mataram. This study uses a classroom action research method with the subjects of the study were children of group A1 with the age of 4-5 years at TK Al Hamidy Mataram in the amount of 10 people. The research instrument used in the study was the observation sheet and documentation. Data analysis in this study uses descriptive qualitative and quantitative analysis. The results of this study indicate that the picture card game has been able to develop social abilities of children aged 4-5 years at the TK Al Hamidy Mataram, which before the picture card game activity was carried out the average value of the child’s social abilities was 62.8%, and after carrying out the activities games with pictorial cards have increased their average score to 81.6%.